An Edge and Fog Computing Platform for Effective Deployment of 360 Video Applications - Rigazzi, Giovanni; Kainulainen, Jani-Pekka; Turyagyenda, Charles; Mourad, Alain; Ahn, Jaehyun (IEEE., 2019)
Immersive video applications based on 360 video streaming require high-bandwidth, high-reliability and low-latency 5G connectivity but also flexible, low-latency and cost-effective computing deployment. This paper proposes a novel solution for decomposing and distributing the end-to-end 360 video streaming service across three computing tiers, namely cloud, edge and constrained fog, in order of proximity to the end user client. The streaming service is aided with an adaptive viewport technique. The proposed solution is based on the H2020 5G-CORAL system architecture using micro-services-based design and a unified orchestration and control across all three tiers based on Fog05. Performance evaluation of the proposed solution shows noticeable reduction in bandwidth consumption, energy consumption, and deployment costs, as compared to a solution where the streaming service is all delivered out of one computing location such as the Cloud.
Keywords: Edge computing; Fog computing; 360 video